2009
DOI: 10.1007/s00216-009-3265-z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of urinary steroid metabolites in calf urine after oral and intramuscular administration of DHEA

Abstract: DHEA (3β-hydroxy-androst-5-en-17-one) is a natural steroid prohormone. Despite a lack of information on the effect, DHEA and other prohormones are frequently used as a food supplement by body-builders. DHEA is suspected for growth promoting abuse in cattle as well. Considering the latter, urine samples from a previous exposure study in which calves were exposed to 1 g DHEA per day during 7 days, were used. The calves were divided in three groups: one orally treated, one intramuscularly injected and a control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…In cattle, it has been reported that cortisol/DHEA ratio increases in lame dairy cows [26] and following transportation of young bulls [28], but decreases in cows with metritis and leucopenia [29], thus revealing conflicting results when evaluating different J o u r n a l P r e -p r o o f stress conditions. Recently, DHEA has been suspected for growth promoting abuse in cattle, and the measurement of DHEA metabolites have been investigated in calf urine [4], in view of the monitoring programs on hormone residues. The assessment of hair DHEA sulfate (HDHEA-S) concentrations in healthy calves may allow not only to investigate possible alteration due to pregnancy disturbances or to poor welfare conditions, but it may represent also a useful tool in the screening strategy to trace abuses with steroids in this species, especially in beef breeds.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In cattle, it has been reported that cortisol/DHEA ratio increases in lame dairy cows [26] and following transportation of young bulls [28], but decreases in cows with metritis and leucopenia [29], thus revealing conflicting results when evaluating different J o u r n a l P r e -p r o o f stress conditions. Recently, DHEA has been suspected for growth promoting abuse in cattle, and the measurement of DHEA metabolites have been investigated in calf urine [4], in view of the monitoring programs on hormone residues. The assessment of hair DHEA sulfate (HDHEA-S) concentrations in healthy calves may allow not only to investigate possible alteration due to pregnancy disturbances or to poor welfare conditions, but it may represent also a useful tool in the screening strategy to trace abuses with steroids in this species, especially in beef breeds.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Cortisol is essential for final intrauterine fetal development and maturation [1], as well as to trigger the process of parturition in species like ruminants [2], but also to drive the transition to the extrauterine life [3] which consists in structural and physiological changes from the last intrauterine stage of development until the end of the neonatal period. DHEA is a natural steroid prohormone, and it is a key intermediate in the biosynthesis of biologically potent androgens and estrogens [4]; it is known to exert neuroprotective effects and to play a balancing role against a wide range of C effects [5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, several research studies have been implemented through the years to test the effect of different growth promoters administered via different routes [18, 28, 34, 35] and to evaluate residual levels and target metabolites. In this work a commercially available ear implant containing trenbolone acetate and estradiol (Revalor-XS) was tested; this formulation is used in the United States in bovine breeding and is able to release a constant amount of hormones over a time period up to 200 days eliminating the need to reimplant the device.…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, the sample preparation procedures for LC-MS/MS are much simpler than for GC-MS/MS, among which are solid phase, liquid-liquid and protein precipitation extractions [8][9][10]. Therefore, LC-MS/MS appears well-suited for the quantification [11][12][13][14][15][16] and characterization [17][18][19][20][21] of steroid glucuronides in different biological matrices such as urine [8][9][10][11][12][13][14][15][16][17][18][19][20][21], serum [2,3] and tissue [22]. Using liquid-liquid extraction, a highly acidic buffer and polar extraction solvent such as ethyl acetate are required [11], resulting in the co-extraction of many other polar compounds which could potentially interfere with the investigated steroid glucuronides and affect the column life time.…”
Section: Introductionmentioning
confidence: 98%
“…The previously reported quantitation methods of steroid glucuronides have been applied to the matrix urine at high steroid concentrations [8][9][10][11][12][13][14][15][16][17][18][19][20][21]. In the present work, we develop a fully validated liquid chromatography-tandem mass spectrometry (LC-MS/MS) method for the simultaneous direct quantitation of androsterone glucuronide (ADT-G), etiocholanolone glucuronide (Etio-G) and androstan-3a, 17b diol 17-glucuronide (3a-diol-17G) in human serum.…”
Section: Introductionmentioning
confidence: 98%